2010
DOI: 10.17925/enr.2010.05.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Molecular Biology of Alzheimer's Disease and Frontotemporal Lobar Degeneration

Abstract: Alzheimer's disease (AD) is the most common cause of dementia in the elderly, whereas frontotemporal lobar degeneration (FTLD) is the most frequent neurodegenerative disorder with a pre-senile onset. The two major neuropathological hallmarks of AD are extracellular amyloid beta plaques and intracellular neurofibrillary tangles. In FTLD the deposition of tau has been observed in a number of cases, but in several brains there is no deposition of tau but instead a positivity for ubiquitin. In some families these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 63 publications
0
15
0
3
Order By: Relevance
“…The dendritic RNA binding protein TDP-43 is a component of intracellular inclusions found in patients with neurodegenerative diseases such as frontotemporal lobe dementia and Alzheimer’s disease (Galimberti and Scarpini, 2010, Wilson et al, 2011). While it is has been suggested that TDP-43 regulates mRNA translation and is localized to dendrites in an activity-dependent manner (Wang et al, 2008a), it is unclear whether dendritic mRNA localization or local translation are dysregulated by altered TDP-43 function.…”
Section: Dysregulated Synaptic Protein Synthesis In Brain Diseasementioning
confidence: 99%
“…The dendritic RNA binding protein TDP-43 is a component of intracellular inclusions found in patients with neurodegenerative diseases such as frontotemporal lobe dementia and Alzheimer’s disease (Galimberti and Scarpini, 2010, Wilson et al, 2011). While it is has been suggested that TDP-43 regulates mRNA translation and is localized to dendrites in an activity-dependent manner (Wang et al, 2008a), it is unclear whether dendritic mRNA localization or local translation are dysregulated by altered TDP-43 function.…”
Section: Dysregulated Synaptic Protein Synthesis In Brain Diseasementioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS), the most common motor neuron disease 1 , and frontotemporal dementia (FTD) 2 , the most frequent presenile onset neurodegenerative disorder, now belong to a class of neurological conditions caused by repeat expansions, owing to the 2011 discovery that an expanded hexanucleotide (GGGGCC) repeat within a non-coding region of the chromosome 9 open reading frame 72 ( C9orf72 ) gene is the major genetic cause of both disorders, collectively referred to as c9FTD/ALS (OMIM *614260). Because repeat expansions causing other neurodegenerative diseases are known to alter epigenetic mechanisms while simultaneously leading to toxic RNA gain-of-function (GOF) and protein loss-of-function (LOF) 3 , researchers now seek to elucidate whether GOF and/or LOF mechanisms contribute to c9FTD/ALS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, tau pathology is present in some FTD cases whereas others lack tau deposition. A large proportion (~20–50%) of FTD cases have a familial component, and mutations in microtubule-associated protein tau and progranulin genes are the most frequent genetic causes (Galimberti and Scarpini, 2010). Interestingly, mutations in the presenilin-1 ( PSEN1 ) and presenilin-2 ( PSEN2 ) genes, which are the major cause of familial AD, have also been implicated in FTD (Mendez and McMurtray, 2006).…”
Section: Introductionmentioning
confidence: 99%